Hemoglobin A1C as an indicator of the accuracy of blood glucose measurement: comparative study of three technologies used for blood glucose measurements - Almarshad, Hassan (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2017)
In previous studies, the accuracy of glucose measurements were found with significant variations in different self-monitoring devices. This study suggests Hemoglobin a1c (Hba1c) to be used as as an indicator for the accuracy of blood-glucose monitoring devices. In this study, the association between the readings of glycohematoglobin HbA1C and the hyperglycemic readings of thirty hyperglycemic patients is used as an indicator of the accuracy of three types of glucometer devices. The association between hyperglycemic readings and the percentage of HbA1C for the same patients was investigated. The results showed significant association between levels of blood glucose and the percentage of HbA1C in three devices with statistically significant ( p < 0.05). Such relationship is suggested to be used as a relative accuracy of various types of blood glucose self-monitoring devices.